Sustainability of novel water treatment technologies in developing countries: Lessons learned from research trials on a pilot continuous flow solar water disinfection system in rural Kenya. (2018) - Mac Mahon, Joanne; Gill, Laurence W.
Abstract: The transition from laboratory research to pilot scale trials can be challenging for novel water treatment technologies. This transition is even more complex for technologies intended for use in a developing country context due to cultural, infrastructural, financial and capacity related challenges. This research looks at the lessons learned from a pilot installation of a continuous CPC solar water disinfection system in a rural community of Kenya. This project was implemented with local and international partners, however the monitoring and evaluation phase collapsed due to the breakdown of these partnerships. A visit to the project site three years after installation revealed significant problems with the system due to drought and flash flooding. A second project phase was funded through crowdfunding in order to rehabilitate the damaged system and provide an alternative water source for the community during periods of drought. Post project evaluation of both project phases showed that the engagement of local implementing partners is essential for ensuring community participation and effective monitoring and evaluation, as the priorities and presence of international implementing partners can easily change in the medium to long term. More external assistance is required for pilot projects using novel technologies than for those using well-established water treatment systems, particularly in terms of operation and maintenance challenges which may arise in the short to medium term. This requirement for external support significantly impacts the sustainability of these interventions. The performance of the continuous flow system while it was in use was found to be satisfactory and feedback from the community regarding operation of the system and quality of water was positive. Both project phases revealed the need for some small design changes, such as inclusion of air-bleed valves, which would significantly improve system operation for future pilot projects. The project experience also illustrated the need for better understanding of the behaviour of both surface and groundwater, given increasingly unpredictable weather patterns as a result of climate change.